Election candidates fuzzy multi-agent recommender system - Janeska sarkanjac, Smilka; Dukovska, Snezana Cerepnalkovska (SAGE Publications, 2013)
In this paper we propose fuzzy multi-agent recommender system for candidates in state elections that is intended to serve to voters as a filter for excess of information on Internet and other media on their election candidates. The recommender system we propose should guide voters to the candidates that suit their preferences, and help them make a choice of a representative by accessing relevant information. For this system we have enrolled computing with words (CW) methodology which main concepts are graduation (linguistic variables) and granulation (a fuzzy set of points drawn together by similarity). Our proposed recommender system is appropriate for application in developing countries, because of its simplicity and its low cost. It can also serve as foundation for future development and sophistication, taking into consideration both technical and political aspects.